Amalgam restorations: rugosimetric analysis using five types of alloys and four polishing techniques (Pesquisa Odontológica Brasileira, 2000)
The authors studied the effect of four different polishing techniques on amalgam restorations made of two conventional and three high-copper alloys. Polishing was performed 168 hours after condensation. The use of multilaminated burs in the superficial finishing of the amalgam samples led to rugosity similar to that of the nonpolished samples. Regarding the utilized alloys, DFL exhibited the highest values of superficial rugosity, meanwhile GS 80 showed the lowest values. Trituration was performed as the manufacturer indicated and amalgam was condensed in a steel matrix fabricated especially for this research. The matrix had a cavity with 4.0 mm in diameter and 2.0 mm in depht. Five minutes after condensation the amalgam surfaces were submitted to sculpture with a steel blade and then to burnishing. After 25 minutes, the amalgam samples were removed with the aid of the matrix screw. Then, 168 hours after condensation, the samples were polished and submitted to rugosimetric tests.